Beyond Bollywood and Broadway : Plays from the South Asian Diaspora - Bose, Neilesh (Book collections on Project MUSE., 2009)
Eleven plays from North America, the UK, and South Africa delve into the vibrant, cosmopolitan theater of the South Asian diaspora. The original and provocative works in this volume, many published here for the first time, explore the experience of diaspora by drawing on cultural references as diverse as classical Indian texts, adaptations of Shakespeare and Homer, current events, and world music, film, and dance. Neilesh Bose provides historical background on South Asian migration and performance traditions in each region, along with critical introductions and biographical background on each playwright.